Persaingan Perdagangan Blue Ocean Kuota Internet Dan Wifi Dalam Perspektif Ekonomi Islam: Aspek Gharar Dan Riba - Muna, Azka Nimal (Jurnal Ilmiah Ekonomi Islam, 2024)
In the business world can not be separated from the name of competition, in competition there are times when it is tight and dense and some are not yet dense, from this research discusses the competition of blue ocean trade in internet quota and WiFi in the perspective of Islamic economics; aspects of gharar and usury, the purpose of this study is none other than to find out with the competition of internet quota and WiFi in terms of Islamic economic perspective, whether there are elements of gharar and usury in the competition. The method used in this research uses descriptive qualitative research methods, researchers try to describe, record, and analyze phenomena that have recently occurred in society, the approach method uses a phenomenological approach. The results of the study found that there is no element of gharar and usury in the blue ocean trade competition that occurs in internet quota and WiFi, from the perspective of Islamic economics this competition is allowed, because there is no element of fraud or additional interest rates that exist in the practices and transactions carried out from internet quota and WiFi. It can be concluded that this blue ocean trade competition is one of healthy competition.